Analisis Komparasi Usaha Agribisnis Antara Pola Tanam Tumpang Sari Tanaman Tomat Dan Cabai Dengan Tomat Monokultur Dan Cabai Monokultur - Tambunan, Ahmad Akbar; Ilvira, Rika Fitri (AGRISAINS: Jurnal Ilmiah Magister Agribisnis, 2025)
This study aims to analyze the comparison of income, efficiency, and use of farming inputs between chili and tomato intercropping patterns and chili and tomato monoculture in Gong Pinto Village, Karo Regency. The method used is a quantitative descriptive method with a case study research type and the research subjects become informants who will provide various information needed during the research process. The results of this study show The results of the study show that the average total production of chili and tomato intercropping farmers reached 5,120.50 kg with an income of Rp. 53,765,250.00 and a total cost of Rp. 28,054,523.83, so that the net income obtained was Rp. 25,710,726.17. Meanwhile, chili monoculture farmers produced an average of 3,850 kg with an income of Rp. 40,425,000.00 and a total cost of Rp. 23,678,125.00, resulting in a net income of Rp. 16,746,875.00. The income per hectare of intercropping is higher than monoculture, which is Rp. 25,710,726.17 compared to Rp. 16,746,875.00. The results of the t-test show a calculated t value of 2.640 which is greater than the t table of 2.262, which confirms that there is a significant difference in income between the two farming systems. This study concludes that intercropping chili and tomato farming is more profitable than chili monoculture, with higher income and statistically significant differences.